Self-management through perceived symptoms impact among patients with nasopharyngeal cancer during phase 1 of cancer trajectory - Che Abdullah, Che Azunie; Saidi, Sanisah; Lee, Siew Pien (EManuscript Technologies, 2020)
Objective: This study is conducted to understand in-depth the self management experience among the patients with nasopharyngeal cancer during the phase 1 of identification of the symptoms. Method: Individual semi-structured interviews were held with patients diagnosed with nasopharyngeal cancer (N=16) in two general hospitals in Malaysia. Data were transcribed and analysed using framework analysis. Four phases of cancer trajectory identified. In this article, themes emerged inphase 1 is in focus. Results: The finding suggest that during phase 1, patients self-manage their early symptoms of nasopharyngeal cancer based on their perception of the impact of the symptoms towards their life, because of the absent of knowledge on nasopharyngeal cancer. Conclusion: Adequate, appropriate knowledge and information provision on nasopharyngeal cancer among public is highly in demand. It is crucial in promoting effective self-management on symptoms identification and subsequently early detection of nasopharyngeal cancer.